2015
DOI: 10.32607/20758251-2015-7-2-42-47
|View full text |Cite
|
Sign up to set email alerts
|

NeuN As a Neuronal Nuclear Antigen and Neuron Differentiation Marker

Abstract: The NeuN protein is localized in nuclei and perinuclear cytoplasm of most of the neurons in the central nervous system of mammals. Monoclonal antibodies to the NeuN protein have been actively used in the immunohistochemical research of neuronal differentiation to assess the functional state of neurons in norm and pathology for more than 20 years. Recently, NeuN antibodies have begun to be applied in the differential morphological diagnosis of cancer. However, the structure of the protein, which can be revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
253
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(272 citation statements)
references
References 40 publications
13
253
1
5
Order By: Relevance
“…We first tested whether wild-type mice with 7 glutamines (Q) in both endogenous Htt alleles ( Htt Q7/Q7 ) develop age-dependent nuclear envelope defects in cortex and striatum, two HD-vulnerable brain regions in which >80% of the cells are neurons detectable with the neuron-specific marker Neuronal Nuclear Antigen (NeuN) (Gusel’nikova and Korzhevskiy, 2015) (Figure S1A). For this, we followed lamin B1, a structural component of the nuclear lamina, as a marker of the nuclear envelope shape and an initial test of nuclear integrity.…”
Section: Resultsmentioning
confidence: 99%
“…We first tested whether wild-type mice with 7 glutamines (Q) in both endogenous Htt alleles ( Htt Q7/Q7 ) develop age-dependent nuclear envelope defects in cortex and striatum, two HD-vulnerable brain regions in which >80% of the cells are neurons detectable with the neuron-specific marker Neuronal Nuclear Antigen (NeuN) (Gusel’nikova and Korzhevskiy, 2015) (Figure S1A). For this, we followed lamin B1, a structural component of the nuclear lamina, as a marker of the nuclear envelope shape and an initial test of nuclear integrity.…”
Section: Resultsmentioning
confidence: 99%
“…The data showed the mRNA level of bIII-tubulin in C17.2 neural stem cells when cultured in DMEM:F12 supplemented with 2% N2 was significantly higher than that cultured in DMEM complete medium and serum-free DMEM culture medium on day 5 [22]. The GFAP and bIII-tubulin been widely recognized as differentiation markers for astrocytes and neurons, respectively [23]. In the present study, we detected the protein expression of bIII-tubulin and GFAP by immunofluorescence staining (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Positive staining for NeuN suggests the neuronal nature of neoplasms and is considered to be a reliable marker for clear cell neoplasms of the central nervous system, which include CN, oligodendroglioma, and clear cell ependymoma [48889]. It has also been reported that positive staining for NeuN correlates with a lower proliferation index [490].…”
Section: Histopathological Analysis and Molecular Pathogenesismentioning
confidence: 99%